2012
DOI: 10.1136/bmjopen-2011-000683
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of a β-1 selective β blocker, bisoprolol, as a first-line antihypertensive in Indian patients diagnosed with essential hypertension (BRIGHT): an open-label, multicentric observational study

Abstract: ObjectivesThis study was aimed to evaluate the efficacy and tolerability of bisoprolol, in Indian patients diagnosed with stage I essential hypertension as first-line drug.DesignThis was an open-label, phase IV, multicentric prospective study.Settings239 outpatient centres across India.ParticipantsAfter ethical approval, patients who were willing to sign informed consent, who are newly diagnosed with JNC VII stage I essential hypertension (systolic blood pressure 140–159 mm Hg or diastolic blood pressure 90–99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…A recent open‐label, multicenter phase 4 study in Indian patients reinforced these findings; significant reductions in SBP, DBP, and heart rate were observed in the majority of patients (96.4%) following 12 weeks of bisoprolol monotherapy. This study also supported the good tolerability of bisoprolol, with mild AEs reported in only 1.9% of patients, no serious AEs reported, and no withdrawals at the request of either the patient or physician …”
Section: Evidence In Support Of Bisoprolol + Amlodipine In Combinationsupporting
confidence: 79%
See 1 more Smart Citation
“…A recent open‐label, multicenter phase 4 study in Indian patients reinforced these findings; significant reductions in SBP, DBP, and heart rate were observed in the majority of patients (96.4%) following 12 weeks of bisoprolol monotherapy. This study also supported the good tolerability of bisoprolol, with mild AEs reported in only 1.9% of patients, no serious AEs reported, and no withdrawals at the request of either the patient or physician …”
Section: Evidence In Support Of Bisoprolol + Amlodipine In Combinationsupporting
confidence: 79%
“…This study also supported the good tolerability of bisoprolol, with mild AEs reported in only 1.9% of patients, no serious AEs reported, and no withdrawals at the request of either the patient or physician. 41 Amlodipine is a dihydropyridine-type CCB that selectively blocks L-type voltage-gated calcium channels in cardiac muscle and vascular smooth muscle. 16 By blocking L-type voltage-gated calcium channels, amlodipine reduces calcium influx and prevents calciumdependent myocyte contraction and vasoconstriction, resulting in an overall decrease in BP.…”
Section: Evidence In Support Of Bisoprolol + Amlodipine In Combinationmentioning
confidence: 99%